2010
DOI: 10.1254/jphs.09362sc
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Sensitive Nucleus Tractus Solitarius Neurons Regulate Sensitivity of the Baroreceptor Reflex in High Sodium–Loaded Rats

Abstract: Baroreceptor and chemoreceptor signals are transmitted to the nucleus tractus solitarius (NTS) via the primary afferent fibers of the glossopharyngeal and vagal nerves, suggesting a role for the NTS in modulating the arterial baroreceptor reflex (baroreflex). The NTS contains numerous neurotransmitters and receptors, including glutamate, GABA, or substance P (1). However, the role of these neurotransmitters in regulatory baroreceptor and chemoreceptor signals is not fully understood. Recently, the enzyme 11β-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Based on the present effect of central MRs, the neurogenic component is partly responsible for MR-dependent dysautonomia and impaired baroreflex in TASK −/− mice. This notion is also reinforced by prior reports demonstrating that the central Aldo/MR signaling plays an important role in regulation of sympathetic drive and baroreflex in the NTS, rostral ventrolateral medulla, and hypothalamic paraventricular nucleus (Masuda et al, 2010; Nakagaki et al, 2012; Zhang et al, 2012; Lincevicius et al, 2015). Due to lack of experimental data in the present study, the contribution of peripheral MRs is not excluded.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Based on the present effect of central MRs, the neurogenic component is partly responsible for MR-dependent dysautonomia and impaired baroreflex in TASK −/− mice. This notion is also reinforced by prior reports demonstrating that the central Aldo/MR signaling plays an important role in regulation of sympathetic drive and baroreflex in the NTS, rostral ventrolateral medulla, and hypothalamic paraventricular nucleus (Masuda et al, 2010; Nakagaki et al, 2012; Zhang et al, 2012; Lincevicius et al, 2015). Due to lack of experimental data in the present study, the contribution of peripheral MRs is not excluded.…”
Section: Discussionsupporting
confidence: 60%
“…Despite the evidence of contribution of G protein-coupled estrogen receptor activation to the non-genomic effects of Aldo (Brailoiu et al, 2013), the majority of Aldo’s effects are exerted through the activation of the mineralocorticoid receptor (MR) (Hermidorff et al, 2017). Accumulated evidence has implicated the importance of Aldo/MR signaling in the pathogenesis of different hypertensive models, including renovascular hypertension (Lincevicius et al, 2015), stroke-prone spontaneous hypertension (Nakagaki et al, 2012) and high salt-loaded hypertension (Masuda et al, 2010). Chronic systemic administration of Aldo/deoxycorticosterone (DOC) elevated arterial pressure in several animal models (Garwitz and Jones, 1982; Chen et al, 1989; Xue et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, no study investigated if aldosterone acting in the hindbrain changes arterial pressure, particularly at the dose that it produces sodium appetite. Studies showing that the MR antagonist spironolactone increased baroreceptor reflex sensitivity in a renovascular hypertension model or that injection of the MR antagonist eplerenone into the NTS increased baroreflex sensitivity in salt-loaded rats suggest that endogenous aldosterone or corticosterone may be involved in the control of baroreflex function (Lincevicius et al, 2015;Masuda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the brainstem, neurons that contain hydroxysteroid dehydrogenase 2 and MRs were present in the nucleus tractus solitarius. 8 In the rostral ventrolateral medulla (RVLM), Zhu et al 9 and Nakagaki et al 10 reported that microinjection of aldosterone into the RVLM increased blood pressure.…”
Section: Introductionmentioning
confidence: 99%